Endoxifen and fulvestrant regulate estrogen-receptor α and related DEADbox proteins. Issue 12 (December 2020) - Asberger, Jasmin; Erbes, Thalia; Jaeger, Markus; Rücker, Gerta; Nöthling, Claudia; Ritter, Andrea; Berner, Kai; Juhasz-Böss, Ingolf; Hirschfeld, Marc
Abstract : Breast cancer (BC) represents the most common type of cancer in females worldwide. Endocrine therapy evolved as one of the main concepts in treatment of hormone-receptor positive BC. Current research focuses on the elucidation of tumour resistance mechanisms against endocrine therapy. In a translational in vitro approach, potential regulatory effects of clinically implemented BC anti-oestrogens on ERα, its coactivators DDX5, DDX17 and other DEADbox proteins as well as on the proliferation markers cyclin D1 and Ki67 were investigated on both the RNA and protein level. BC in vitro models for hormone-receptor positive (MCF-7, T-47D) and hormone-receptor negative cells (BT-20) were subjected to endocrine therapy. Anti-oestrogen-dependent expression regulation of target genes on the transcriptional and translational level was quantified and statistically assessed. Endocrine therapy decreases the expression levels of Ki67, cyclin D1 and ERα in hormone-receptor positive cells. In the hormone-receptor negative cells, the three parameters remained stable after endocrine therapy. Endoxifen triggers a downregulation of DDX5 and DDX23 in MCF-7 cells. Fulvestrant treatment downregulates the expression levels of all investigated DEADbox proteins in MCF-7 cells. In T-47D cells, endoxifen and fulvestrant lead to a decrease of all target gene expression levels. Interestingly, endocrine therapy affects DEADbox RNA expression levels in BT-20 cells, too. However, this result could only be confirmed for DDX1, immunocytologically. The investigated DEADbox proteins appear to correlate with the oestrogen-dependent tumourigenesis in hormone-receptor positive BC and show expression alterations after endocrine treatment.